Homestays - community programme or alternative accommodation? a re-evaluation of concept and execution - Jabil Mapjabil,; Suriani Che Ismail,; Badariah Ab Rahman,; Tarmiji Masron,; Ruzila Ismail,; Rosmiza Mohd Zainol, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Homestay programmes - which form a part of Community-based tourism (CBT) vital in the development agenda of Third World Countries- provide tourists with a unique opportunity to experience the atmosphere, lifestyle practices and activities of rural communities in the countryside. The Ministry of Tourism and Culture, Malaysia has drawn up a set of guidelines and requirements for operating a homestay program that must be adhered to before approval is granted. The question that has arisen is whether homestay programs as practised in Malaysia truly present visitors with the opportunity to experience the host community’s lifestyle, or merely serve as an alternative form of accommodation. This article overviews the various scenarios and dilemmas faced in implementing the homestay programmes in the Malaysian context, the causes that lead to its ‘abuse’, and some practical solutions that may be proposed to address the arising issues and challenges in an integrated manner.